Harmoni Manusia dan Laut: Tindakan Sosial Masyarakat Suku Bajau dalam Mempertahankan Tradisi Selamatan Leu (Laut) - Hermawan, Hery; Budhi, Setia (Prodi Sosiologi FISIP ULM, 2026)
Amid the rapid advancement of technology, local traditions such as selamatan leu among the Bajau ethnic community in Rampa Lama Village, Kotabaru Regency, have undergone significant changes and are increasingly threatened with extinction. Many local traditions have experienced transformation or are at risk of disappearing, including selamatan leu (sea thanksgiving ritual) practiced by the Bajau community in Rampa Lama Village, Kotabaru Regency. This study aims to understand the responses of the younger generation to cultural shifts resulting from the dominant use of mobile phones in everyday life. This research employs a qualitative method with a phenomenological approach, utilizing participant observation, in-depth interviews, and documentation. Data were analyzed using the Manual Data Analysis Procedure (MDAP), which includes field notes, transcripts, coding, categories, themes, and memos. The findings reveal four forms of social action within the community: instrumental rational action, value-rational action, affective action, and traditional action. These forms of social action represent the community’s motivations in preserving the selamatan leu tradition. This study highlights the importance of maintaining local traditions in the face of modern challenges posed by the rapid development of digital technology. Academically, this research contributes to expanding studies on social action among coastal communities. Practically, it emphasizes the importance of preserving the selamatan leu tradition and promoting awareness of sustainable marine ecosystem conservation.